The relationship between scapular endurance and core endurance in elite amputee football players - Gunaydin, G. (Baltic Journal of Health and Physical Activity, 2021)
Background: Body structure constitutes a kinetic chain with thoracolumbar fascia and this chain may induce a relationship between scapular and spinal stabilizers. Amputee soccer players use crutches during the game and, considering that the crutch use may also activate different muscle groups, the possibility of the relationship between scapular and spinal stabilizers becomes important for organizing training programs. The aim of this study is to determine the relationship between scapular endurance and core endurance in elite amputee players. Material and methods: Fifteen male amputee national football team players took part in the study. The players` scapular endurance was evaluated by a dynamometer, and the modified side bridge test was used to evaluate core endurance. Results: The relationship between scapular and core endurance was investigated via the Linear Regression Model. The analysis revealed a positive association between scapular endurance and core endurance (B: 0.501, ß: 0.561, p: 0.029). Conclusions: This study shows the relationship between scapular and core endurance in amputee football players. Given the assumptions about scapular and core endurance weakness, including scapular muscle exercises along with core exercises in the training programs might be useful for improving performance.